EDITORIAL (American Journal of Islam and Society, 1991)
We report with great sadness the death of Victor Danner, a friend ofIslam and Muslims, a graduate of Georgetown and Harvard, and Chairmanof the Department of Near Eastern Languages and Cultures at Indiana University,BloomingtOn, Indiana. Darner's latest publication was The Islamic Traditiontion: An Introduction. W have been inviting Muslim anti non-Mush scholarsfrom time to time to present their responses to the International Instituteof Islamic Thought’s caIl for the Islamization of Knowledge. So far, we havebeen very lucky to have had the opportunity to listen to the late Fazlur Rahman,Sayyed H. Nasr, Abdulaziz Sachedina and others who joined this debateat the IIIT headquarters. Some of these responses have been published invarious issues of AJISS.Victor Danner treated us to his response on May 15, 1989, when hepresented his paper, which appears in this issue under the title of “WesternEvolutionism in the Muslim World,” at the IIIT headquarters. In this article,he launches an eloquent plea for the rediscovery and reexploration of thevarious schools of thought in Islam and their subsequent adaptation to theneeds and circumstances faced by contemporary Muslims. He reminds usthat past attempts at reform by Muslim intellectuals were based on a readaptationof the traditional techniques of Islam which, when presented in a freshmanner as a solution to the needs faced by their own contemporaries, gavethe doctrine of tawhid “a powerful radiance that had a convincing allure toit.” This is followed by an examination of the origins of evolutionary thinkingin the West, how its eventual acceptance and spread throughout the Westultimately displaced Christian beliefs and institutions on a massive scale,and how the resulting secular civiIization produced by it is threatening tosweep aside and destroy traditional Islamic civilization. In closing, he stateshis hope that a better understanding of this phenomenon among the Muslimintelligentsia and the people at large will cause them to wake up to this dangerand begin to work for the preservation of the ”traditional culture of Islam.”Our first article in this issue is by Imaduddin Khalil, and addresses theQur’an’s relationship vis-his modem science. After ruling out the Qur’anas a book or textbook of scientific knowledge, he proceeds to discuss thephilosophy and aims of science and the basic principles of Islam. He beginswith the role of humanity on earth as the khaEfuh of Allah, moves on tothe principles of tawazun (balance) and taskhir (an Islamic concept statingthat the world and nature have been made subservient to humanity), andcloses with the principle of a link between creation and the Creator. Khalilviews the Qur’anic methodology as being a “methodology of discovery” of ...